2013
DOI: 10.1007/s10661-013-3201-8
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate statistical techniques for the assessment of seasonal variations in surface water quality of pasture ecosystems

Abstract: This study investigates the applicability of multivariate statistical techniques including cluster analysis (CA), discriminant analysis (DA), and factor analysis (FA) for the assessment of seasonal variations in the surface water quality of tropical pastures. The study was carried out in the TPU catchment, Kuala Lumpur, Malaysia. The dataset consisted of 1-year monitoring of 14 parameters at six sampling sites. The CA yielded two groups of similarity between the sampling sites, i.e., less polluted (LP) and mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…They reported that total organic carbon, dissolved organic carbon, total nitrogen, dissolved nitrate and nitrite, orthophosphate, alkalinity, salinity, Mg, and Ca were the most important parameters in assessing variations of water quality in the river. HCA, DA, and PFA were applied for the assessment of seasonal variations in the surface water quality of tropical pastures in Kuala Lumpur [17]. The study was conducted with a dataset consisting of one-year monitoring of 14 parameters at six sampling sites.…”
Section: Application Of Multivariate Statistical Methodsmentioning
confidence: 99%
“…They reported that total organic carbon, dissolved organic carbon, total nitrogen, dissolved nitrate and nitrite, orthophosphate, alkalinity, salinity, Mg, and Ca were the most important parameters in assessing variations of water quality in the river. HCA, DA, and PFA were applied for the assessment of seasonal variations in the surface water quality of tropical pastures in Kuala Lumpur [17]. The study was conducted with a dataset consisting of one-year monitoring of 14 parameters at six sampling sites.…”
Section: Application Of Multivariate Statistical Methodsmentioning
confidence: 99%
“…This is different from the cluster obtained in the dry season, where S3 was grouped along with S4 in cluster 2. It is evident that the season affects the water quality of this stream . This may be due to the flow of runoff from S3 during rainfall events common in the rainy season.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, CA may reduce the number of samples, so only representative sites from each cluster are used (not all sampling stations). This can reduce the cost of the analysis . CA was useful for giving a first exploratory indication of the difference between the studied sites and also a second exploratory indication of the difference between the dry and rainy seasons for the polluted area in the vicinity of paper industry .…”
Section: Resultsmentioning
confidence: 99%
“…Hierarchical cluster analysis was carried out to classify the wetland according to their nutrient status and geospatial location seasonally. Ward's method of linkage was used, with the squared Euclidean distance, as a measure of similarity, to determine the distance between clusters [24].…”
Section: Gis and Statistical Analysismentioning
confidence: 99%